2007
DOI: 10.2474/trol.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Study on Decomposition of Multialkylated Cyclopentane Oil with Sulfur-Containing Additive on the Nascent Steel Surface

Abstract: Effect of di-tert-dodecyl disulfide as an additive on decomposition of MAC oil on the nascent surface of bearing steel 52100 was investigated. After the removal of surface contamination layer, active sites were generated, on which tribochemical decomposition of MAC oil occurred. The additive prolonged the induction period of the decomposition. Hydrogen and gaseous hydrocarbons desorbed as tribochemical reaction products. Desorption rate of hydrogen and gaseous hydrocarbons increased proportionally with sliding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Vacuum tribometer tests conducted using vacuum‐stable lubricants give the opportunity to investigate lubricant degradation in situ by linking the tribometer to a chemical analyser such as a mass spectrometer. Consequently, gaseous reaction products like hydrogen and low molecular fragments can be detected and correlated to lubricant decomposition . These reactions leading to the release of such low molecular compounds are usually catalysed by the oxide‐free steel surface formed in tribological contact .…”
Section: Introductionmentioning
confidence: 99%
“…Vacuum tribometer tests conducted using vacuum‐stable lubricants give the opportunity to investigate lubricant degradation in situ by linking the tribometer to a chemical analyser such as a mass spectrometer. Consequently, gaseous reaction products like hydrogen and low molecular fragments can be detected and correlated to lubricant decomposition . These reactions leading to the release of such low molecular compounds are usually catalysed by the oxide‐free steel surface formed in tribological contact .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these additives can as well reduce the degradation of the lubricant under tribological contact. 22,29,30…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these additives can as well reduce the degradation of the lubricant under tribological contact. 22,29,30 Since it is not clearly understood which parameters influence the hydrogen permeation, and the cause of white etching areas (WEA), the tribologically induced hydrogen permeation is examined in detail in this study. Therefore, a special cell was developed and manufactured to measure the hydrogen permeation as a function of tribological parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, saturated hydrocarbons like n-hexane can hardly adsorb on nascent steel surfaces at room temperature, because they do not have functional groups which interact chemically with the surfaces. However, it has been found that synthetic hydrocarbon oil of MAC (Multi Alkylated Cyclopentane) tribochemically decomposed readily on nascent steel surfaces at mechanical contact resulting in formation of hydrogen and methane [11][12][13][14][15]. This result can be explained by the activity of nascent steel surfaces as well as high temperature caused by mechanical contacts.…”
Section: Introductionmentioning
confidence: 99%